Recycling of Plastics from Cable Waste from Automotive Industry in Poland as an Approach to the Circular Economy - Dorota Czarnecka-Komorowska (MDPI AG, 2021)
This paper presents the contemporary problems of polymer waste recycling, mainly recycling cables from end-of-life vehicles. The authors developed a new material based on mixed polymer waste (ASR) modified with a ductile polymer, mainly recycled low-density polyethylene (rLDPE), to produce moisture-resistant boards with beneficial mechanical properties. The ASR-based compositions without and with homogenization process—including physical, chemical, and shear-assisted compatibilization—were successfully applied and verified by evaluating final recycled product properties. The results showed that recycled polyethylene (rLDPE) was effective as a modifier increasing tensile modulus and flexural strength compare to an ASR mixture. It was found that the adding 5 wt % of polyethylene-grafted maleic anhydride (PE-g-MAH) as a compatibilizer to the ASR mixture significantly increases the homogenization of the components in the ASR matrix. The optimal solution for management cable waste is the manufacture of ASR composites with homogenization using an internal mixer the adding 20 wt % of rLDPE and 5 wt % of PE-g-MAH to the mixed plastics cable waste. The results obtained demonstrate that the hot-pressing with the pre-blending with rLDPE and compatibilizer of the ASR based waste provides a high gain in mechanical and usage properties, enabling the circular economy of plastics from automotive cables.